2010
DOI: 10.1007/s12576-009-0078-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repeated lengthening contractions on skeletal muscle adaptations in female rats

Abstract: We examined the adaptation of plantar flexor muscles of female rats to 6 weeks (5 days/week) of lengthening contractions. After repeated lengthening contractions, a decrease in myofiber area of gastrocnemius medialis (26%) was accompanied by an increase in extracellular matrix (ECM) (42%) and collagen content (30.9%) without changes in muscle mass. Decrease in myofiber area (13%) and muscle mass of soleus (19%) was associated with increased collagen content (28%) and ECM (15%). Relative number of soleus myofib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…Several studies have examined the effects of cyclical loading and repeated muscle strains on extracellular matrix content, including collagen [7], [8], [17], [22], [24], [25], [26], [27], [28], [29]. There is also data concerning the influence of physical exercise, mechanical loading andcyclical loading on CTGF and TGFB1 production in musculoskeletal tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have examined the effects of cyclical loading and repeated muscle strains on extracellular matrix content, including collagen [7], [8], [17], [22], [24], [25], [26], [27], [28], [29]. There is also data concerning the influence of physical exercise, mechanical loading andcyclical loading on CTGF and TGFB1 production in musculoskeletal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Stauber and colleagues have shown that repeated muscle strains at fast velocities (lengthening contractions stimulated electrically) resulted in fibrotic myopathy with increased collagen content, collagen cross-links and non-contractile tissues, while repeated strains at low velocities did not [25], [26], [27], [28]. Factors and mechanisms of repetitive strain-induced fibrosis in tissues are still under investigation, but appear to involve CTGF and transforming growth factor beta-1 (TGFB1) [29], [30], [31], [32], [33].…”
Section: Introductionmentioning
confidence: 99%
“…The measurement of muscle mass can be confounded by a number of factors including intramuscular fat, which can be influenced by specific genetic factors during growth (33), and connective tissue, which can be affected by physical activity (34). Myofibrillar protein content accurately reflects the pool of functional proteins that account for the ability of muscles to perform work (35).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, TA and GA muscles are located in the anterior and posterior hindlimb compartment, respectively, and were thus immobilized in a lengthened and shortened position, respectively. Connective tissue thickening that prevailed during immobilization (49) was greater when lengthening was applied (37).…”
mentioning
confidence: 99%